2010
DOI: 10.1109/tit.2010.2048502
|View full text |Cite
|
Sign up to set email alerts
|

On the Index Coding Problem and Its Relation to Network Coding and Matroid Theory

Abstract: The index coding problem has recently attracted a significant attention from the research community due to its theoretical significance and applications in wireless ad-hoc networks. An instance of the index coding problem includes a sender that holds a set of information messages X = {x1, . . . , x k } and a set of receivers R. Each receiver ρ = (x, H) ∈ R needs to obtain a message x ∈ X and has prior side information comprising a subset H of X. The sender uses a noiseless communication channel to broadcast en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
312
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(314 citation statements)
references
References 29 publications
2
312
0
Order By: Relevance
“…due to related extensions such as secure broadcast, broadcasting with side information, and index coding [14], [15]). Several practical codes have been designed.…”
Section: B Relation To Prior Work 1) Deterministic Broadcast Channelsmentioning
confidence: 99%
“…due to related extensions such as secure broadcast, broadcasting with side information, and index coding [14], [15]). Several practical codes have been designed.…”
Section: B Relation To Prior Work 1) Deterministic Broadcast Channelsmentioning
confidence: 99%
“…The algorithm will back off window according to the priority to dynamically adjust the node, compared with DCF back off algorithm for BEB, not simply fixed length increases or decreases, so as to ensure the high priority packets with smaller back off window after the collision, which can seize the channel faster, but also will not cause nodes back off value is too large [11] .…”
Section: The Send Window Adjustmentmentioning
confidence: 99%
“…In [21], it was shown that any network coding problem can be reduced to an index coding problem and that a network coding problem admits a linear solution if and only if a linear index code of a specific length (determined by the network coding problem) exists for the corresponding index coding problem. This relationship was extended to include nonlinear codes in [22].…”
Section: Introductionmentioning
confidence: 99%